2011
DOI: 10.1039/c0jm03833d
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive finite size effects on the phase diagram and metal–insulator transitions of tungsten-doped vanadium(iv) oxide

Abstract: The influence of finite size in altering the phase stabilities of strongly correlated materials gives rise to the interesting prospect of achieving additional tunability of solid-solid phase transitions such as those involved in metal-insulator switching, ferroelectricity, and superconductivity. We note here some distinctive finite size effects on the relative phase stabilities of insulating (monoclinic) and metallic (tetragonal) phases of solid-solution W x V 1Àx O 2 . Ensemble differential scanning calorimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
173
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(186 citation statements)
references
References 65 publications
13
173
0
Order By: Relevance
“…[9][10][11][12][13] Therefore, much effort has been made to modulate the MIT by various approaches such as strain engineering, 14,15 ionic liquid gating, [16][17][18] electric field-induced oxygen vacancy, 19 and chemical doping. [20][21][22][23][24][25] In terms of chemical doping, using metal elements such as tungsten during growth can dramatically change the transition properties 20,26 , but it is an irreversible process. Recently, we have demonstrated that reversible doping with atomic hydrogen alters the electronic phase transition.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] Therefore, much effort has been made to modulate the MIT by various approaches such as strain engineering, 14,15 ionic liquid gating, [16][17][18] electric field-induced oxygen vacancy, 19 and chemical doping. [20][21][22][23][24][25] In terms of chemical doping, using metal elements such as tungsten during growth can dramatically change the transition properties 20,26 , but it is an irreversible process. Recently, we have demonstrated that reversible doping with atomic hydrogen alters the electronic phase transition.…”
mentioning
confidence: 99%
“…50 K/at.% for the nano structures. 14,15 The mechanism behind this MIT transition has been debated for several decades and it has attracted great attention from various research areas. Two different points of views, as being more a Motttype transition characterized by strong electron-electron correlations 16,17 , or more a Peierls-type transition triggered by the structural V dimerization, have been supported experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the T c of VO 2 (M) can be tuned by doping with W, Mo, Nb, F atoms, etc. or their mixtures [4][5][6][7][8][9][10][11]. These features make VO 2 to be suitable for applications [5,9,10,[12][13][14][15][16][17] in optical switches, storage medium, smart window coatings, temperature-sensing devices, laser protection, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a lot of methods [4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21][22][23][24], such as RF sputtering, pulsed laser, deposition vacuum evaporation, physical vapor deposition, thermolysis, chemical vapor deposition, sol-gel, hydrothermal synthesis and so on, have been developed to synthesize VO 2 (M) or doped VO 2 (M). All of above methods, the hydrothermal method [5][6][7]11] has been paid increasing attention to synthesize W-doped VO 2 (M) because of its uncomplicated route and mass production recently.…”
Section: Introductionmentioning
confidence: 99%